2015
DOI: 10.1016/j.ccc.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Overload

Abstract: Most critically ill patients experience external or internal fluid shifts and hemodynamic instability. In response to these changes, intravenous fluids are frequently administered. However, rapid losses of administered fluids from circulation and the indirect link between the short-lived plasma volume expansion and end points frequently result in transient responses to fluid therapy. Therefore, fluid overload is a common finding in intensive care units. The authors consider the evidence of harm associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 114 publications
3
87
0
1
Order By: Relevance
“…Loss of normal glycocalyx and endothelial integrity secondary to cytotoxic injury causes a markedly disrupted systemic fluid balance leading to a deleterious cycle of intravascular fluid loss, interstitial edema, impaired vascular tone, and plasma protein loss. 4,6 This is congruent with our finding that patients with normal albumin levels prior to allo-HCT had a reduced risk of FO. These events likely influence the use and overuse of IV fluids that may worsen excessive FO.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Loss of normal glycocalyx and endothelial integrity secondary to cytotoxic injury causes a markedly disrupted systemic fluid balance leading to a deleterious cycle of intravascular fluid loss, interstitial edema, impaired vascular tone, and plasma protein loss. 4,6 This is congruent with our finding that patients with normal albumin levels prior to allo-HCT had a reduced risk of FO. These events likely influence the use and overuse of IV fluids that may worsen excessive FO.…”
Section: Discussionsupporting
confidence: 87%
“…5 FO in critically ill patients exerts its effects through disruption of organ architecture, vascular drainage, and oxygen perfusion secondary to interstitial edema. 6 FO is common among patients during the early post allogeneic hematopoietic cell transplantation (allo-HCT) period, even in the absence of sepsis or critical illness. Moreover, its influence on outcomes after allo-HCT has been poorly understood until recently.…”
Section: Introductionmentioning
confidence: 99%
“…This interstitial edema may mediate toxic effects in multiple organs. The capillary vascular endothelium may play an important role in the balance between extracellular and intravascular fluids, 13 which could make FO part of a spectrum of endothelial damage disorders that includes sinusoidal obstructive syndrome, thrombotic microangiopathy, and idiopathic pneumonia syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting fluid overload, with thresholds of 10% excess from the admission weight, is associated with an incremental risk of mortality in patients with and without AKI [79]. Fluid overloaded patients have an increased risk of AKI [80, 81], and there is reduced renal recovery from AKI [82]. Several studies have shown that both the magnitude and persistence of fluid overload are associated with worse outcomes, suggesting that prevention and correction of fluid accumulation are modifiable risk factors to improve survival.…”
Section: Rrt In Severe Aki: An Overviewmentioning
confidence: 99%